Effect of Implant Angulation on Attachment Retention in Mandibular Two‐Implant Overdentures: A Clinical Study. (10th January 2013) - Jabbour, Zaher; Fromentin, Olivier; Lassauzay, Claire; Abi Nader, Samer; Correa, José A.; Feine, Jocelyne; de Albuquerque Junior, Rubens F.
Abstract Purpose Attachment wear can affect the performance of mandibular two‐implant overdentures (IODs). This prospective clinical study aimed to investigate the effect of interimplant angulation on the retention achieved by two attachment systems at different time points within 1 year of wearing IODs. Materials and Methods Twenty‐four patients (mean age = 73.2 years; standard deviation (SD) = 3.1) wearing IODs opposed by conventional maxillary complete dentures were randomly assigned to two groups in two‐by‐two crossover design. Retentive Anchor (RA) and Locator (LA) were installed in the IODs of both groups for 1 year, sequentially. Coronal and sagittal interimplant angulation were measured on posterior–anterior and lateral cephalometric radiographs. Retention was measured at baseline, 1 week, 3, 6, and 12 months postattachment installation. Data were analyzed using mixed models with α = 0.05. Results Mean coronal and sagittal interimplant angulations were 4.6 (SD = 2.9) and 3.5 (SD = 2.6) degrees, respectively. Only with LAs a statistically significant decrease was found in retention (average 1.1 Newton; standard error = 0.38; p = .007) per 1 degree increased sagittal interimplant angulation. Conclusions Increased interimplant angulation appears to have higher impact on the retention of LA than of RA attachments. The effect of larger interimplant angulation on the loss of attachment retention and its clinical implications should be further assessed.